Traits of Historical Research in Islamic Architectural Studies: Islamic Art and Architecture (650-1250) - Shahani, Mohammadhossein (Universitas Muhammadiyah Surakarta, 2025)
This paper investigates the traits of historical research in the context of Islamic architectural studies. For this purpose, it focuses on the distinguished book